European Union and health policy: mechanisms of europeanization of healthcare systems - Seretis, Stergios; Sotiriou, Sotiris; Pantoularis, Ioannis; Poulimas, Michalis; Kondilis, Elias (The Greek Review of Social Research, 2021)
Europeanization, defined as the process of designing and transferring European Union (EU) policies to member states, is a topical issue affecting multiple areas of policy practice. The aim of this paper is to explore the width and depth of Europeanization in health systems and develop a classification framework of the mechanisms of Europeanization most commonly applied in health policy. Our results indicate that Europeanization is a gradually widening institutional practice in healthcare. The most recent economic crisis was marked by a clear shift from horizontal non-mandatory Europeanization practices to vertical and mandatory ones, increasing significantly EU’s intervention in domestic health policies.